Anaemia Association with Intestinal Parasitic Infection in Pregnant Women Attending Antenatal Clinic at Tribhuvan University Teaching Hospital - Sapkota, Laxmi; Maharjan, Mahendra (Journal of Advanced College of Engineering and Management, 2018)
Anaemia is the common problem during pregnancy in developing countries like Nepal.  A total of 200 stool samples for parasitic infection and their haemoglobin level data were collected from the pregnant women visiting TUTH. The overall prevalence of intestinal parasitic infection and anaemic rate among pregnant women was found to be 35% and 50%. Among 100 anaemic pregnant women 58 women were infected with intestinal parasites. The association of anaemia with intestinal parasitic infection was statistically significant (P > 0.05). The most dominant parasite among anaemic pregnant women was A. lumbricoides followed by H. nana. Total five different types of intestinal parasites were identified in this study. Among them A. lumbricoides (30.5%), H. nana 6(3%), E. histolytica 5(2.5%), T. trichiura 2(%) and S. stercoralis 2(1%) respectively. Pregnant women with single parasitic infection were found to be 64(32%) and multiple infection were 6(3%). Intensity of parasitic infection found to be 17(8.8%), 34 (17.0%) and 17 (9.5%) for light, moderate and heavy infection. Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 41-47